Development of an optimum end-effector with a nano-scale uneven surface for non-adhesion cell manipulation using a micro-manipulator. (25th September 2015) - Horade, M; Kojima, M; Kamiyama, K; Kurata, T; Mae, Y; Arai, T
Abstract: In order to realize effective micro-manipulation using a micro-manipulator system, an optimum end-effector is proposed. Cell-manipulation experiments using mouse fibroblast cells are conducted, and the usability of the proposed end-effector is confirmed. A key advantage of the micro-manipulator is high-accuracy, high-speed 3D micro- and nano-scale positioning. Micro-manipulation has often been used in research involving biological cells. However, there are two important concerns with the micro-manipulator system: gripping efficiency and the release of gripped objects. When it is not possible to grip a micro-object, such as a cell, near its center, the object may be dropped during manipulation. Since the acquisition of exact position information for a micro-object in the vertical direction is difficult using a microscope, the gripping efficiency of the end-effector should be improved. Therefore, technical skill or operational support is required. Since, on the micro-scale, surface forces such as the adsorption force are greater than body forces, such as the gravitational force, the adhesion force between the end-effector and the object is strong. Therefore, manipulation techniques without adhesion are required for placed an object at an arbitrary position. In the present study, we consider direct physical contact between the end-effector and objects. First, the design and materials of the end-effector for micro-scale manipulation were optimized, and an end-effector with an optimum shape to increase the grip force was fabricated. Second, the surface of the end-effector tip was made uneven, and the adhesion force from increasing on the micro-scale was prevented. When an end-effector with an uneven surface was used, release without adhesion was successful 85.0% of the time. On the other hand, when an end-effector without an uneven surface was used, release without adhesion was successful 6.25% of the time. Therefore, the superiority of a structure with an uneven surface was demonstrated, and high-accuracy cell manipulation without sliding during handling and without adhesion was performed successfully.